THE IMPORTANCE OF ANALYZING PERFORMANCE INDICATORS WITHIN THE PRODUCTION PROCESS - de Oliveira, Gabryela Ceballos; Dias, Fernando Henrique (Revista Interface Tecnológica, 2023)
The analysis of performance indicators plays a crucial role in improving the efficiency of the production process in a company. This article highlights the importance of these indicators in measuring organizational success and aiding in decision-making. The results obtained confirm the relevance of indicator analysis in identifying bottlenecks and deviations in the production process, suggesting that a more in-depth analysis can contribute to improving performance, efficiency, and productivity within the company. However, it is essential to consider challenges such as operator training and proper selection of data analysis tools. The correct implementation of proposed solutions and continuous monitoring are crucial to ensure the effectiveness of the improvements. In summary, performance indicator analysis is crucial for identifying improvement opportunities and enhancing production processes, driving business success.